Black-Eyed Pea Diet Alleviates High-Density Lipoprotein Cholesterol In Menopausal Women; Randomized Clinical Trial Study - Handi Wiradharma; Pande Made Dwijasa; Maharani Maharani (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2022)
Introduction: Menopause is defined as the last menstruation cycle in women. Estrogen concentration in menopausal women was decreased and altered the lipid metabolism profiles. Menopausal women reportedly have a high risk of cardiovascular disease, arthritis, diabetes mellitus, and stroke. This study focused on the effect of the black-eyed pea diet on the lipid profiles in menopausal women. Material and Methods: A randomized clinical study was performed to analyzedd the effect of the black-eyed pea diet on lipid profiles. Fifty-four menopausal women were selected as respondents and classified into two groups, black-eyed pea diet and placebo. Black-eyed pea diet treatment was performed by consuming black-eyed powder containing 67.5 mg of isoflavones and were monitored in week – 0 and week – 12 after treatment. Lipid profile of black-eyed pea diet and placebo in 12 weeks monitoring showed no significant value. After 12 weeks of treatment, total cholesterol and triglyceride were higher than before treatment. Results: Interestingly, the black-eyed pea diet increased the HDL and lowered the LDL after 12 weeks of treatment. Conclusion: This study concluded that black-eyed pea improved lipid profile, especially in elevating HDL level and decreasing LDL level in 12 weeks consumption.